2014
DOI: 10.1680/wama.13.00046
|View full text |Cite
|
Sign up to set email alerts
|

Velocity field in a reservoir in the presence of an air-core vortex

Abstract: The velocity field in a reservoir in the presence of surface vortices was experimentally studied. Experiments were performed with a horizontal intake and with a constant submerged depth and two different intake Froude numbers.The spline smoothing method was used to improve the graphical presentation of the measured data. Results are presented and compared in different horizontal sections in the reservoir. A downward conical flow over the intake axis and an upward one below the intake axis were observed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Their experiments showed that the horizontal plate had better performance in eliminating vortices [11]. Sarkardeh et al (2013) experimentally investigated the velocity field in a tank in the presence of an air-core vorticity. They determined the prevailing domains of vertical and horizontal velocities [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their experiments showed that the horizontal plate had better performance in eliminating vortices [11]. Sarkardeh et al (2013) experimentally investigated the velocity field in a tank in the presence of an air-core vorticity. They determined the prevailing domains of vertical and horizontal velocities [12].…”
mentioning
confidence: 99%
“…Sarkardeh et al (2013) experimentally investigated the velocity field in a tank in the presence of an air-core vorticity. They determined the prevailing domains of vertical and horizontal velocities [12]. Khanarmuei et al (2014) investigated the effect of intake withdrawal direction on the vortex strength.…”
mentioning
confidence: 99%
“…All vorticities were limited to the inner core zone and the outer zone was free of vorticity. During the last few decades, different studies experimentally modelled flow field in the presence of vortices to understand the behaviour of this phenomenon 3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Besides experimental studies, researchers also tried to numerically simulate vortex formation in the reservoirs [19][20][21][22][23][24][25][26][27] .…”
mentioning
confidence: 99%
“…

It is my pleasure to welcome you to the June issue of Water Management, which brings together a selection of papers, briefings and discussions on a diverse range of interesting topics. The subsequent four papers focus on complex flow dynamics generated in stilling basins by submerged jets (Zhang et al, 2014) and at reservoir intakes by free surface vortices (Sarkardeh et al, 2014); sanitation issues associated with portable sewage systems (Khan et al, 2014b); and water quality modelling in clean water distribution networks (Seyoum and Tanyimboh, 2014).The accurate determination of water surface profiles for gradually varied flow (GVF) is a classic hydraulic problem of significant importance to water engineers interested in determining the upstream and downstream influence of in-stream structures or works. The subsequent four papers focus on complex flow dynamics generated in stilling basins by submerged jets (Zhang et al, 2014) and at reservoir intakes by free surface vortices (Sarkardeh et al, 2014); sanitation issues associated with portable sewage systems (Khan et al, 2014b); and water quality modelling in clean water distribution networks (Seyoum and Tanyimboh, 2014).

The accurate determination of water surface profiles for gradually varied flow (GVF) is a classic hydraulic problem of significant importance to water engineers interested in determining the upstream and downstream influence of in-stream structures or works.

…”
mentioning
confidence: 99%
“…In the final paper of the issue, Sarkardeh et al (2014) present results from a scaled experimental study of velocity fields generated adjacent to a horizontal reservoir intake in the presence of a surface, air-core vortex. Such vortices are known to result in operational problems for hydropower schemes including system vibrations, decreased turbine efficiency, debris entrainment and trash screen blockage at the intake, and reduced turbine longevity.…”
mentioning
confidence: 99%